Reverberações: a sociabilidade do rádio em época de whatsapp - Brito, Maira Rossin Gioia de (2020)
This work investigates how the radio's sociability occurs when the audience makes use of technological resources such as the WhatsApp messaging application. Using the case study method of exploratory quality, the analysis has messages received by CBN during the truckers strike in 2018 and at the beginning of the COVID-19 pandemic in 2020 as study objects. The research aims to analyze the intrinsic aspects in the content generated and which involve audience modality, purpose and behavior. For this, the study discards the categorization proposals which are based on technical aspects and proposes a division of messages based on concepts related to users of media. The starting point are the reflections brought by SHIRKY (2011) and HAN (2018), such as media coverage, demedication, personal and / or common motivation, waves of indignation, coordinated action and civic motivation. The results allow us to see how the use of the application has enhanced the sociability of the radio, listeners to choose between constituting a participatory audience or just receiving the program.